E-Service Impacting Supply Chain Performance - Yen-Na Lam (Hochschule für Angewandte Wissenschaften Hamburg, 2020)
The beginning of the twenty-first century shows the confluence of two powerful, long-term trends in the business world: the shifting of the economy from goods to services and the rapid expansion of electronic networks. The landscape of organizational service offers is undergoing a fundamental change. New communication technologies, new media, the Internet, and devices carrying new functionalities are shaping services nowadays. The confluence of services and the expanding electronic delivery technology has given rise to the new era of e-service. Companies have adopted new information and communication technology to offer e-services to their customers. However, only few studies are available focusing on the impact that e-service specifically has on supply chain performance. This paper aims at filling this gap. It examines significant opportunities for supply chain improvements that develop along with the growth of eservice. Therefore, the Balanced Scorecard model will be applied. This paper examines the impact of e-service on the two perspectives most relevant for this research. Results show that in the perspective of internal processes, we find potential improvements and challenges in the concepts of multi-channel business, mobile employment, tracking and tracing and e-procurement services. In the perspective of customer performance, organizations benefit from online customer service and self-service technologies. Possible improvements and deficits are reflected in performance metrics.